Profile of Health Based on Body Mass Index, Blood Pressure, and Blood Sugar Levels in the Elderly - Maria Karolina Selano; Emirensiana Anu Nono; Kristiana Prasetia Handayani; Maria Dolorosa Peni Sogen; Gregorius Tsiompah; Oke Dwi Astuti (GLOBAL HEALTH SCIENCE GROUP, 2025)
Diabetes mellitus (DM) is an escalating global health issue, characterised by its increasing prevalence and the significant complications it entails. Effective management of blood glucose levels is a critical component in preventing DM-related complications. This study aims to analyse the health profiles of elderly individuals based on Body Mass Index (BMI), blood pressure, and blood glucose levels. An observational cross-sectional design was employed, involving data collection at a single point in time to identify relationships between variables. The sample consisted of 120 respondents aged 60 and above residing in the Puskesmas Kagok area. Purposive sampling was utilised to select respondents based on inclusion criteria, specifically targeting elderly individuals willing to participate and without any medical conditions necessitating specialised care. The data revealed that the average BMI of respondents was 25.3, with 25% classified as normal weight, 50% as overweight, and 25% as obese. In terms of blood pressure, 58.33% of respondents were found to be hypertensive, while 41.67% were within the normal range. Additionally, the average random blood glucose level was 205 mg/dL, with 33.33% of respondents exhibiting glucose levels ≥ 200 mg/dL, indicating a high risk of diabetes. Demographic characteristics indicated that 66.7% of respondents were female, and 75% had been diagnosed with diabetes for over five years. Educational attainment varied, with 51.6% having completed secondary education and 31.7% possessing higher education qualifications. Notably, 46.6% of respondents were not engaged in employment. These findings highlight a high prevalence of overweight, hypertension, and elevated blood glucose levels among the elderly population in the Puskesmas Kagok area, underscoring the necessity for preventative measures and management of non-communicable diseases within this age group. It is anticipated that this research will provide valuable insights for the development of health programmes tailored to the needs of the elderly.